2019
DOI: 10.1002/jso.25628
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for lymph node metastasis in early‐stage gastric cancer: Toward tailored lymphadenectomy

Abstract: Background: The aim of this study was to develop a prediction model for the presence and location of lymph node metastasis (LNM) in early gastric cancer. Method:We reviewed medical records of 4 929 patients who underwent radical gastrectomy for early gastric cancer. Variables of age, sex, lymphatic invasion, depth of invasion, location, gross type, differentiation, and tumor size were analyzed.Logistic regression analysis was used to determine independent predictors of LNM at each LN station.Result: Overall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Previous studies have explored the risk factors for LNM of EGC patients and established corresponding prediction models (8)(9)(10)(11). Previous study reported that the female sex is an independent risk factor for LNM in patients with EGC (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the risk factors for LNM of EGC patients and established corresponding prediction models (8)(9)(10)(11). Previous study reported that the female sex is an independent risk factor for LNM in patients with EGC (12).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of middle third invasion was defined according to the pathology report, when the epicenter of a cancer located in the upper third area involved the middle third area. In previous studies, factors related to LN metastasis in early gastric cancer included tumor size, depth of invasion, histological type, presence or absence of vascular invasion, and lymphatic invasion [ 10 11 12 ]. Tumor location, depth, size, and histological type are also known to affect the incidence and distribution of LN metastasis in advanced gastric cancer [ 13 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, several recent studies demonstrated the prognosis in young gastric cancer patients was equal to or better than that of the older gastric cancer patients. [1][2][3][4] Authors showed the overall 5-year survival for the older group was significantly lower than that for the younger group. 5 And there was no significant difference in 5-year cancer-specific survival for both groups.…”
Section: Editorialmentioning
confidence: 99%